2014
DOI: 10.1007/s12185-014-1538-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aprepitant in preventing nausea and vomiting due to high-dose melphalan-based conditioning for allogeneic hematopoietic stem cell transplantation

Abstract: High-dose melphalan has been gaining recognition as a highly emetogenic agent used in hematopoietic stem cell transplantation (HSCT). The aim of this retrospective study was to elucidate the efficacy of aprepitant in preventing high-dose melphalan-induced emesis. Sixty patients who received melphalan (70 mg/m(2)/day, 2 days) and fludarabine (125 mg/m(2)/day, 5 days) as conditioning for allogeneic HSCT for hematological malignancies, and who received ondansetron and methylprednisolone as an antiemetic prophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
5
0
5
Order By: Relevance
“…34 Aprepitant is a neurokinin-1 antagonist that inhibits the action of substance P. When combined with a corticosteroid and a serotonin antagonist, it relieves nausea and vomiting in chemotherapy patients. 34,36 Corticosteroids such as dexamethasone are potent antiemetics thought to inhibit prostaglandin synthesis. 34 Capsaicin cream applied to the abdomen has also been reported to relieve symptoms, possibly through an interaction between the TRPv1 receptor and the endocannabinoid system.…”
Section: How Can Cannabis Both Cause and Prevent Vomiting?mentioning
confidence: 99%
“…34 Aprepitant is a neurokinin-1 antagonist that inhibits the action of substance P. When combined with a corticosteroid and a serotonin antagonist, it relieves nausea and vomiting in chemotherapy patients. 34,36 Corticosteroids such as dexamethasone are potent antiemetics thought to inhibit prostaglandin synthesis. 34 Capsaicin cream applied to the abdomen has also been reported to relieve symptoms, possibly through an interaction between the TRPv1 receptor and the endocannabinoid system.…”
Section: How Can Cannabis Both Cause and Prevent Vomiting?mentioning
confidence: 99%
“…It was reported that aprepitant remarkably reduced the incidence of CINV [8,9,11]. Many studies on antiemetic strategy in HSCT revealed efficacy and safety of NK-1 inhibitors in a combination of 5-HT3RA and dexamethasone ("triplet") during the conditioning chemotherapy [47][48][49][50][51][52][53][54][55][56][57][58][59]. A randomized placebocontrolled trial on CINV during high-dose chemotherapy in autologous (auto-) or allogeneic (allo-) HSCT reported that complete response rates, defined as no emesis with no or mild nausea, were 81.9% in triplet arm and 65.8% in doublet arm (P < 0.001) [56].…”
Section: Nk1ramentioning
confidence: 99%
“…Even in HSCT with reduced-intensive conditioning (RIC) regimens, which are usually regarded as having a lower risk for nausea, it is unclear whether we should use antiemetics for HEC or MEC. As only few studies have evaluated antiemetic treatment focusing on a specific conditioning regimen in HSCT [ 41 , 47 , 48 , 54 , 58 , 59 , 61 , 70 , 75 ], more evidence to develop a better antiemetic strategy for each conditioning regimen is needed.…”
Section: Each Antiemetic Drug In Hsctmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] With regard to patients undergoing allogeneic HSCT, one prospective and a few retrospective studies have assessed the impact of the addition of aprepitant and found benefit. 14,15,21,22 The interim analysis of a randomized placebo-controlled trial of patients receiving cyclophosphamide-containing conditioning regimens found a higher complete response (CR) for the aprepitant arm. 16 Historically, studies specifically evaluating aprepitant in patients undergoing autologous HSCT have numerous limitations including small numbers of subjects; retrospective or non-comparison study designs; and importantly, variability in outcomes assessed.…”
Section: Introductionmentioning
confidence: 99%